2014
DOI: 10.1080/00071668.2014.938020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation withGynura procumbens(Merr.) on egg yolk cholesterol, excreta microflora and laying hen performance

Abstract: 1. The present study investigated the effects of dietary supplementation with Gynura procumbens on egg yolk and serum cholesterol and triglycerides, excreta microflora, laying performance and egg quality. 2. A total of 160 Hy-Line Brown layers (45 weeks old) were randomly assigned into 4 treatments on the basis of laying performance. Each treatment had 4 replicates with 10 birds each. 3. Dietary treatments were basal diet supplemented with 0 (control), 2.5, 5.0 and 7.5 g/kg diet G. procumbens during 56-d feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…and Escherichia coli. 35 Another experiment with weanling pigs show that Aqueous Hypoglycaemic effect 21 Hepato protective effect 45 "essential oils" alpha-pinene, 3-carene, limonene 13 Anti-inflammatory 13 Anti-nociceptive effects 13 Methanol Hepatoprotetive effect 44 Methanol →Ethyl Acetate…”
Section: Antihypertensive Effectmentioning
confidence: 99%
“…and Escherichia coli. 35 Another experiment with weanling pigs show that Aqueous Hypoglycaemic effect 21 Hepato protective effect 45 "essential oils" alpha-pinene, 3-carene, limonene 13 Anti-inflammatory 13 Anti-nociceptive effects 13 Methanol Hepatoprotetive effect 44 Methanol →Ethyl Acetate…”
Section: Antihypertensive Effectmentioning
confidence: 99%
“…Aydin, Karaman, Cicek & Yardibi (2008) reported a significant reduction of cholesterol in the egg yolk of laying hens fed diets with seeds of Nigella sativa. Similarly, the inclusion of Gynura procumbens or olive leaf (Olea europea) in diets reduced egg yolk cholesterol in laying hens (Cayan & Erener, 2015;Lokhande et al, 2014) due to the secondary metabolites of these plants (v.gr. saponins).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that saponins from Karaya (Sterculina urens) (Afrose, Hossain, Maki & Tsujii, 2010a), Yucca schidigera (Wang & Kim, 2011), Ilex latifolia (Feng et al, 2015), and Alfalfa (Medicago sativa) (Fan, Du, Zhou, Shi & Wang, 2015;Liang et al, 2015) reduce egg and blood plasma cholesterol, and they regulate the expression of genes associated to cholesterol metabolism. According to many of these studies, there is a close relationship between plasma and egg cholesterol in laying hens, because egg cholesterol decreases as plasma cholesterol decreases (Afrose, Hossain, & Tsujii, 2010b;Fan et al, 2015;Lokhande et al, 2014).…”
Section: Introductionmentioning
confidence: 99%